Joaquim Nabuco, a política escravista e o abolicionismo - Costa, Milton Carlos [UNESP] (My University, 2014)
In this article initially we tried to show the criticism made by Nabuco about the imperial slave politics, then your search overcoming of slavery through the abolitionist campaign. The two moments of labor established the confrontation of his positions with the treatment given to the topics studied by historiography in the variety of their views.

Neste artigo procuramos inicialmente mostrar a crítica feita por Nabuco da política escravista imperial e, depois, a sua busca da superação do escravismo através da campanha abolicionista. Nos dois momentos do trabalho estabelecemos o confronto de suas posições com o tratamento dado aos temas estudados pela historiografia na variedade de seus pontos de vista.
Keywords: Joaquim Nabuco; Slave holding policy; Abolitionism; Joaquim Nabuco; Política escravista; Abolicionismo